2017
DOI: 10.1038/s41598-017-04595-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-parasite therapy drives changes in human visceral leishmaniasis-associated inflammatory balance

Abstract: Visceral leishmaniasis (VL) remains a major public health problem worldwide. Cytokine balance is thought to play a critical role in the development of this disease. Here, we perform a prospective exploratory study addressing whether simultaneous assessment of circulating levels of different lipid mediators and cytokines could highlight specific pathways involved with VL pathogenesis. VL patients displayed substantial increases in serum levels of Prostaglandin F2α (PGF2α), Leukotriene B4 (LTB4), Resolvin D1 (Rv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
4
20
0
4
Order By: Relevance
“…This finding suggests that L. major -infected macrophages probably evolved the ability to inhibit a deleterious innate inflammatory immune response (Fleming et al, 2015 ); alternatively, this anti-inflammatory response could be a consequence of the effort by host macrophages to control parasite infection (Dillon et al, 2015 ). Consistent with these findings, in the sera of patients during the active phase of visceral leishmaniasis it was detected a significant increase in inflammatory mediators including LTB4, RvD1, PGF2α (PGF2α), IL-1β, IL-6, IL-8, IL-10, IL-12p70, and TNF-α, and a decreased level of TGF-β1 (Araújo-Santos et al, 2017 ).…”
Section: Transcriptomics Contribution To Understanding the Host Respomentioning
confidence: 53%
See 3 more Smart Citations
“…This finding suggests that L. major -infected macrophages probably evolved the ability to inhibit a deleterious innate inflammatory immune response (Fleming et al, 2015 ); alternatively, this anti-inflammatory response could be a consequence of the effort by host macrophages to control parasite infection (Dillon et al, 2015 ). Consistent with these findings, in the sera of patients during the active phase of visceral leishmaniasis it was detected a significant increase in inflammatory mediators including LTB4, RvD1, PGF2α (PGF2α), IL-1β, IL-6, IL-8, IL-10, IL-12p70, and TNF-α, and a decreased level of TGF-β1 (Araújo-Santos et al, 2017 ).…”
Section: Transcriptomics Contribution To Understanding the Host Respomentioning
confidence: 53%
“…The identification of a set of soluble biomarkers in host tissue has been exploited using sera of individuals with visceral leishmaniasis (Solcà et al, 2016 ; Araújo-Santos et al, 2017 ). A recent study screened a variety of soluble molecules and identified a set of inflammatory biomarkers that grouped together under a hierarchical cluster analysis (Araújo-Santos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease results from an inability of macrophages to kill the parasite (6). A complex signaling network of molecules produced by macrophages and T and B lymphocytes, with pro-and anti-inflammatory roles, produces an inflammatory status that is responsible for the many clinical manifestations of the disease without achieving control of parasite growth (5,7). The bone marrow, liver and spleen are the most affected internal organs (8).…”
Section: Introductionmentioning
confidence: 99%